743. Severity and Costs of Respiratory Syncytial Virus and Bronchiolitis Hospitalization in Commercially Insured Preterm and Term Infants Before and After the 2014 American Academy of Pediatrics Guidance Change on Immunoprophylaxis. (26th November 2018) - Krilov, Leonard R; Fergie, Jaime; Goldstein, Mitchell; Rizzo, Christopher; Brannman, Lance; McPheeters, Jeffrey; Korrer, Stephanie; Burton, Tanya; Sharpsten, Lucie
Abstract: Background: In 2014, the American Academy of Pediatrics (AAP) stopped recommending respiratory syncytial virus (RSV) immunoprophylaxis in infants 29–34 weeks gestational age (wGA) without chronic lung disease (CLD) or congenital heart disease (CHD). This study examined the impact of this guidance change on the severity and costs of first year of life RSV hospitalizations (RSVH) and all-cause bronchiolitis hospitalizations (BH) among preterm (PT) vs. term infants in the 2014–2016 seasonal years relative to the 2011–2014 seasonal years. Methods: Infants aged <1 year between July 1, 2011 and June 31, 2016 were identified from commercial insurance claims in the Optum Research Database. Diagnosis codes identified births of term and 29–34 wGA infants without CLD, CHD, or other health problems, RSVH, and BH. Length of stay (LOS), admission to the intensive care unit (ICU), and use of mechanical ventilation (MV) captured RSVH and BH severity. Costs were adjusted to 2015 USD. Results: A total of 362, 382 births (29–34 wGA and term without major health problems) were identified, of which 13, 666 (3.8%) were PT. RSVH and BH were more severe among PT infants in 2014–2016 vs. 2011–2014, with a greater mean LOS (RSVH: 6.8 vs. 4.7 days, P = 0.008; BH: 7.2 vs. 4.6, P = 0.021), a higher proportion of infants admitted to the ICU (RSVH: 42.4% vs. 25.3%, P = 0.014; BH: 39.1% vs. 23.7%, P = 0.009), and increased use of MV (RSVH: 14.1% vs. 6.1%, P = 0.067; BH: 14.8% vs. 5.3%, P = 0.013). Among term infants, LOS and ICU admissions were similar between 2014–2016 and 2011–2014 ( P > 0.05), but there was an increased use of MV in the 2014–2016 season (RSVH: 6.9% vs. 4.2%, P = 0.009; BH: 6.3% vs. 3.7%, P = 0.003). Mean costs per hospitalization were greater for PT infants in 2014–2016 compared with 2011–2014 (RSVH: $29, 382 vs. $16, 572, P = 0.059; BH: $26, 101 vs. $15, 896, P = 0.047), whereas mean term hospitalization costs were similar (RSVH: $15, 011 vs. $15, 472, P = 0.705; BH: $14, 555 vs. $14, 603, P = 0.957). Conclusion: RSVH and BH severity and per-hospitalization costs (higher among PT infants relative to term infants) increased following the 2014 AAP immunoprophylaxis guidance change. The increases are likely explained by more frequent RSV hospitalizations among higher-risk 29–34 wGA infants in 2014–2016. Funded by AstraZeneca Disclosures: L. R. Krilov, AstraZeneca/MedImmune: Consultant, Research grant and Research support. J. Fergie, AstraZeneca/MedImmune: Consultant and Speaker's Bureau, Research grant and Research support. M. Goldstein, AstraZeneca/MedImmune: Consultant, Research grant and Research support. C. Rizzo, AstraZeneca: Employee, Salary and Stocks. L. Brannman, AstraZeneca: Employee, Salary and Stocks. J. McPheeters, Optum: Employee, Salary. AstraZeneca: Research Contractor, Consulting fee. S. Korrer, Optum: Employee, Salary. AstraZeneca: Research Contractor, Consulting fee. T. Burton, Optum: Consultant and Employee, Salary. AstraZeneca: Research Contractor, Consulting fee. L. Sharpsten, Optum: Employee, Salary. AstraZeneca: Research Contractor, Consulting fee.